Employee Wellbeing Programs and Their Impact on Organizational Productivity in the Digital Era - Nur Alifah; Agus Rohmat Hidayat; Kyra Kholilah Wardaniyah (Jurnal Syntax Admiration, 2026)
The digital era has fundamentally transformed the nature of work, creating new demands on employee health, engagement, and cognitive capacity while simultaneously offering unprecedented technological tools to address these challenges. This study investigates the relationship between structured Employee Wellbeing Programs (EWPs) and organizational productivity across ASEAN economies, drawing on secondary panel data from 10 ASEAN member states (2015–2023) and an integrative review of 20 empirical studies. Employing a Composite Wellbeing Index (WBI) constructed via Principal Component Analysis (PCA) and a two-stage fixed-effects panel regression model, the study finds that EWP adoption is a significant and robust predictor of organizational productivity (β = 0.43, p < 0.001), with the technology and services sectors reporting the highest productivity gains (14.6% and 13.2% respectively) from wellbeing investment. Digital tool integration, mental health support, and physical wellness programs collectively account for 75% of explained productivity variance. Governance quality and HRM strategic orientation significantly moderate the EWP–productivity relationship. The mean ASEAN Composite Productivity Index (CPI) rose from 58.1 in 2015 to 68.0 in 2023, with high-WBI firms consistently outperforming low-WBI counterparts by 15–20 index points throughout the observation period. The findings advance theoretical understanding of the human capital–productivity nexus in digital-era organizations and provide actionable recommendations for ASEAN policymakers and corporate HR practitioners.